Ring & Ride: Lizenz zum Selberfahren. Was Kunden vom Mobilen Ticketing der nächsten Generation erwarten. - Maertins, Christian; Knie, Andreas (Deutscher Verkehrs-Verl., 2008)
Der öffentliche Verkehr wird moderner und einfacher. Das Internet erleichtert Kunden die Information, mit Handy und Chipkarte wird die Nutzung flexibler. Nach verschiedenen Projektphasen im Mobilen Ticketing ist die Modellvielfalt groß. Herkömmliche Tarife und neue Technologien bestimmen die Diskussion. Wie ist es um Kundenakzeptanz und Potenziale bestellt und können neue Zielgruppen für den öffentlichen Verkehr erreicht werden.

All the large integrated transport networks nowadays facilitate the cashless and paperless purchase of tickets, plus obligatory documents, for travel by local public transport. The next stage offers ticketing via mobile telephones as an attractive proposition since travel over selected routes - plus appropriate fares - can be determined automatically. The research project 'Ring & Ride' applied a check-in/check-out logic wherely customers begin and end their journey by using a mobile telephone, irrespective of the use of one or several means of transport for travel within a city/town or over long distances. GSM records data about the services used, followed by a monthly invoice that covers all the journeys undertaken. This pilot scheme's technical functionality and customers' acceptance have been investigated, and results have shown that fares and rates have been worked out correctly for ninety-four per cent of all journeys. The flexibility and convenience of using a mobile telephone emphasizes a person's independence of the peculiarities of public transport infrastructure, of the range of services on offer and of the requirement to be familiar with the system. Consequently, this has convinced the majority of customers. In particular, occasional users of public transport plus new multi-modal groups of travellers can thus be reached.
Ring & Ride: a new initiative.
Keywords: Öffentlicher Verkehr; Verkehrstechnik; Verkehrstechnologie; Mobilität; ÖPNV; Feldversuch; Abrechnung; Innovation; E-Ticketing; Fahrschein; Fahrkarte; Internet; Mobiltelefon; Fahrpreis; Kundenbefragung; Zielgruppe